Transcriptomic Data Analyses Reveal That Sow Fertility-Related lincRNA NORFA Is Essential for the Normal States and Functions of Granulosa Cells - Du, Xing (Front Cell Dev Biol, 2021)
NORFA, the first lincRNA associated with sow fertility, has been shown to control granulosa cell (GC) functions and follicular atresia. However, the underlying mechanism is not fully understood. In this study, RNA-seq was performed and we noticed that inhibition of NORFA led to dramatic transcriptomic alterations in porcine GCs. A total of 1,272 differentially expressed transcripts were identified, including 1167 DEmRNAs and 105 DEmiRNAs. Furthermore, protein–protein interaction, gene-pathway function, and TF–miRNA–mRNA regulatory networks were established and yielded four regulatory modules with multiple hub genes, such as AR, ATG5, BAK1, CENPE, NR5A1, NFIX, WNT5B, ssc-miR-27b, and ssc-miR-126. Functional assessment showed that these hub DEGs were mainly enriched in TGF-β, PI3K-Akt, FoxO, Wnt, MAPK, and ubiquitin pathways that are essential for GC states (apoptosis and proliferation) and functions (hormone secretion). In vitro, we also found that knockdown of NORFA in porcine GCs significantly induced cell apoptosis, impaired cell viability, and suppressed 17β-estradiol (E2) synthesis. Notably, four candidate genes for sow reproductive traits (INHBA, NCOA1, TGFβ-1, and TGFBR2) were also identified as potential targets of NORFA. These findings present a panoramic view of the transcriptome in NORFA-reduced GCs, highlighting that NORFA, a candidate lincRNA for sow fertility, is crucial for the normal states and functions of GCs.